2010
DOI: 10.1186/1471-2164-11-227
|View full text |Cite
|
Sign up to set email alerts
|

Survey of transcripts expressed by the invasive juvenile stage of the liver fluke Fasciola hepatica

Abstract: BackgroundThe common liver fluke Fasciola hepatica is the agent of a zoonosis with significant economic consequences in livestock production worldwide, and increasing relevance to human health in developing countries. Although flukicidal drugs are available, re-infection and emerging resistance are demanding new efficient and inexpensive control strategies. Understanding the molecular mechanisms underlying the host-parasite interaction provide relevant clues in this search, while enlightening the physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 87 publications
0
50
0
Order By: Relevance
“…Despite the limited amount of sequence data available in the databases for Fasciola, there have been a number of recent efforts to analyse the transcriptome and proteome of the fluke, at different stages in the life cycle (Gourbal et al, 2008;Cancela et al, 2010;Hernández-González et al, 2010;Young et al, 2010Young et al, , 2011. The technologies have the potential to identify proteins, based on sequence homology with known molecules in other organisms.…”
Section: Identification Of Drug and Vaccine Candidates: The "-Omics" mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the limited amount of sequence data available in the databases for Fasciola, there have been a number of recent efforts to analyse the transcriptome and proteome of the fluke, at different stages in the life cycle (Gourbal et al, 2008;Cancela et al, 2010;Hernández-González et al, 2010;Young et al, 2010Young et al, , 2011. The technologies have the potential to identify proteins, based on sequence homology with known molecules in other organisms.…”
Section: Identification Of Drug and Vaccine Candidates: The "-Omics" mentioning
confidence: 99%
“…Fasciola hepatica secretes a variety of cathepsins-10 cathepsin B proteases and at least 5 cathepsin L proteases. The individual cathepsins show a pattern of expression during the mammalian phase of the life cycle that is strongly linked to the migration and development of the fluke, with the cathepsin B proteases predominating in the earlier stages, while the cathepsin L proteases are the only forms produced by the adult stage (Cancela et al, , 2010Robinson et al, 2008aRobinson et al, ,b, 2009Beckham et al, 2009;see Fig. 2 in Robinson et al, 2009).…”
Section: Identification Of Drug and Vaccine Candidates: The "-Omics" mentioning
confidence: 99%
“…During the invasion process the invasive NEJs are confronted with different environments in their passage from the intestine to the liver. It has been demonstrated that changes in gene expression underlie the early stages of invasion (Cancela et al, 2008(Cancela et al, , 2010 but little is known of how these processes are regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Later, three cathepsin B isotypes were identified from stage-specific cDNA libraries of F. gigantica and named FgCatB1, FgCatB2, and FgCatB3 (Meemon et al 2004). The orthologous cathepsin B isotypes (CB1, CB2, CB3) were then identified in juvenile F. hepatica (Cancela et al 2008(Cancela et al , 2010. RT-PCR and phylogenetic analyses demonstrated that these isotypes were stagespecific (Meemon et al 2004;Cancela et al 2008;Smooker et al 2010).…”
Section: Cathepsin Bmentioning
confidence: 99%